INTEGRATIVE APPROACH TO CORRECTING NEUROCOGNITIVE DISORDERS IN CHILDREN WITH ASD USING PSYCHOMOTOR THERAPY - T.B. Irmukhamedov (KONFERENSIYALAR, 2025)
Introduction.  It  is  known  that  the  leading  criteria  for  assessing  a  child's health are the state of mental and motor functioning. A delay in the development of  motor  activity,  in  turn,  can  cause  a  delay  in  the  mental  development  of  the child,  since  these  two  important  areas  of  activity  represent  the  most  important basis in understanding the surrounding picture of the world.